Millennials’ continuous purchase drivers for halal Japanese restaurant - Yasera, Yuciko Ichwanda; Hati, Sri Rahayu Hijrah (Faculty of Business & Economics, Universitas Islam Indonesia, 2025)
Purpose – This study examines how consumption values influence attitudes toward halal certification and continuous purchase intention in Japanese restaurants in Indonesia, using millennial perceptions. It explores the impact of consumption value on millennial consumer behavior following the government’s halal certification mandate.Methodology – A quantitative approach was used to collect data from 225 social media-active respondents who had dined at halal-certified Japanese restaurants. Structural Equation Modeling-Partial Least Squares (SEM-PLS) analyzes the relationships between consumption values, attitudes, and continuous purchase intention.Findings – Food safety concerns, health consciousness, prestige value, affordance value, visibility value, and emotional value positively influenced attitudes toward halal certification and continuous purchase intention. However, price value did not have a significant direct effect on continuous purchase intention, although it showed a different result in relation to attitudes toward halal certification. Attitude and health consciousness were the most influential antecedent variables affecting continuous purchase intention among millennials.Implications – These findings provide valuable insights for halal food businesses, particularly Japanese restaurant operators, by identifying the key consumption values that shape Muslim millenial consumers’ eating preferences. Understanding these factors can help businesses and policymakers refine their marketing strategies to attract and retain halal-conscious consumers in Indonesia’s growing industry.Originality – This study provides empirical evidence of how different consumption values shape consumer attitudes and purchasing behavior in halal-certified Japanese restaurants, addressing a gap in the understanding of the effects of government regulations on halal-conscious consumer decisions.